PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP LOYALITAS KONSUMEN CV. SABANI INDONESIA SURABAYA - setyowati, endang; septyan, mohammad (JEM17: Jurnal Ekonomi Manajemen, 2017)
ABSTRACTThesis entitled "The impact of service quality and product quality to consumers loalitas CV. Sabani Indonesia Surabaya "aims to determine the effect of service quality and product quality terehadap consumer loyalty simultaneous partial and see what's most dominant influence. In this study, researchers used a questionnaire to determine the perception of respondents was 50, a data analysis technique used in this study were using multiple linear regression with correlation test, F test and t test tools. The test results of this study are obtained calculation results of multiple linear regression is Y = 1,876 + 0, 105 kpl + 0.172 mortgages where all these variables have positive influence and direction of the dependent variable namely customer loyalty CV. Sabani Indonesia Surabaya. The test results simultaneously obtained Fhitung 71.299 71.299 which means Fhitung> Ftabel 3.20, or can be seen from the level of significance of 0.000 <0.05 (Î± = 5%). While partially obtained Thitung Quality of service (KPL) = 2,865 Thitung Product Quality (KPR) = 4,348, thus Thitung> Ttabel (2.01174). Thus the hypothesis which states that the quality of service and product quality simultaneously or partially significant effect on consumer loyalty CV. Sabani Indonesia Surabaya proven true. Variable quality of products (mortgage) has the most dominant influence on the satisfaction of members of the cooperative as it has the largest regression coefficient is 0.172 compared to 0.105 service quality variables.Keywords: quality of service, product quality, customer loyalty